Making or Breaking Metal‐Dependent Catalytic Activity: The Role of Stammers in Designed Three‐Stranded Coiled Coils. Issue 46 (2nd September 2020) - Pinter, Tyler B. J.; Manickas, Elizabeth C.; Tolbert, Audrey E.; Koebke, Karl J.; Deb, Aniruddha; Penner‐Hahn, James E.; Pecoraro, Vincent L.
Abstract: While many life‐critical reactions would be infeasibly slow without metal cofactors, a detailed understanding of how protein structure can influence catalytic activity remains elusive. Using de novo designed three‐stranded coiled coils (TRI and Grand peptides formed using a heptad repeat approach), we examine how the insertion of a three residue discontinuity, known as a stammer insert, directly adjacent to a (His)3 metal binding site alters catalytic activity. The stammer, which locally alters the twist of the helix, significantly increases copper‐catalyzed nitrite reductase activity (CuNiR). In contrast, the well‐established zinc‐catalyzed carbonic anhydrase activity ( p ‐nitrophenyl acetate, pNPA) is effectively ablated. This study illustrates how the perturbation of the protein sequence using non‐coordinating and non‐acid base residues in the helical core can perturb metalloenzyme activity through the simple expedient of modifying the helical pitch adjacent to the catalytic center. Abstract : The addition of a stammer discontinuity within a de novo designed 3SCC containing a symmetric (His)3 metal binding site enhances copper nitrite reductase activity and ablates zinc esterase activity. These results suggest catalytic activity of designed α‐helical systems can be modulated by inclusion of discontinuity insertions and deletions.